EFL Students' achievement in the TOEFL academic reading section: The case of an English Education program in a private University - Hera Hartati; Anggia Pratiwi; Herysa Oktawati (Jurnal Sinar Edukasi, 2026)
This study was conducted to evaluate the reading proficiency of English students on the Test of English as a Foreign Language (TOEFL). Quantitative descriptive research was implemented in this investigation. The investigation was conducted within the English Education Program of Merangin University. Forty-six students comprised the candidate population of graduates. Total sampling was used. Data were collected using the TOEFL book for four sets and the students' answer sheets. After conducting an analysis of the data, the study established a correlation between the item specification of the reading section in the TOEFL book and the responses of the students, specifically the topic and main idea, inference, vocabulary (synonym), details, and reference. Subsequently, the study also considered the conversion score in the TOEFL evaluation guide. The researcher discovered that students had low reading achievements on the TOEFL as a result of this research. Identifying the topic and main idea was the least successful accomplishment. The second category was inference, the third was reference, the fourth was vocabulary, and the final category was details. This study endeavors to focus on the reading subject and the methods of facilitating students' comprehension of the various components of reading. It is also necessary to teach effective reading strategies. For students, it is essential to enhance their reading proficiency, engage with reading passages, and engage in additional practice.